Nilai-Nilai Nasionalisme KH. Sholeh Darat Dalam Tafsir Faiḍ Al-Rahmān - Salsabily, M. (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Nationalism is an understanding to love one's own nation and state and jointly defend and perpetuate the identity, integrity, prosperity, and strength of the nation itself. One of the scholars who have a nationalist spirit is KH. Sholeh Darat. In this paper, we will discuss the values of KH's nationalism. Sholeh Darat in the interpretation of Faid Al Rahman. In this paper, the author uses a type of library research, namely one of the works of Faid Al-Rahmäān's commentary. The result of this research is that there are three values of KH's nationalism. Sholeh Darat in Faid Al Rahman's interpretation, namely the value of love for the homeland, the value of unity and unity and the value of pluralism.